Fresno County Bar Associations' 105th Annual Bar Banquet - Watkins, Howard::::::::: (1987)
Judy Soley receiving a plaque of appreciation from Fresno County Bar Association President Herbert Levy Recognized Judy Soley's year of service on the Fresno County Bar Association Board of Directors as Immediate Past President.